Exploring the Chemoselectivity towards Cysteine Arylation by Cyclometallated Au(III) Compounds: New Mechanistic Insights - Thomas, Sophie R. (Chembiochem, 2020)
To gain more insight into the factors controlling efficient cysteine arylation by cyclometallated Au(III) complexes, the reaction between selected gold compounds and different peptides was investigated by high‐resolution liquid chromatography electrospray ionization mass spectrometry (HR‐LC‐ESI‐MS). The deduced mechanisms of C−S cross‐coupling, also supported by density functional theory (DFT) and quantum mechanics/molecular mechanics (QM/MM) calculations, evidenced the key role of secondary peptidic gold binding sites in favouring the process of reductive elimination.